Exploring in New Testament fields - Habershon, Ada Ruth, 1861-1918 (London, UK Pickering and Inglis)
Includes bibliographical references and index.
Brethren writer. Donated by Mr R.C. Croucher.
Keywords: Bible N.T. -- introductions